2012
DOI: 10.4103/2152-7806.103868
|View full text |Cite
|
Sign up to set email alerts
|

Extent of intraoperative muscle dissection does not affect long-term outcomes after minimally invasive surgery versus open-transforaminal lumbar interbody fusion surgery: A prospective longitudinal cohort study

Abstract: Background:Minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) versus open TLIF, addressing lumbar degenerative disc disease (DDD) or grade I spondylolisthesis (DS), are associated with shorter hospital stays, decreased blood loss, quicker return to work, and equivalent short- and long-term outcomes. However, no prospective study has assessed whether the extent of intraoperative muscle trauma utilizing creatinine phosphokinase levels (CPK) differently impacts long-term outcomes.Methods:Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
1
13
2
Order By: Relevance
“…The increased value of the microscopic group was significantly higher than that of the percutaneous transforaminal endoscopic group, and the difference was statistically significant, which was essentially consistent with the previous research results. In addition, some scholars have found that the postoperative serum CPK content of male patients is much higher than that of females due to their higher muscle tissue content [18] ; however, in this study, there was no significant difference between the serum CPK content of males and females, whether before or after surgery. For patients with high risk of lumbar spine surgery, some scholars suggest taking dynamic and systematic measurements of CPK contents and establishing a standard measurement interval to assess the degree of muscle injury more effectively [19] .…”
Section: Serum Creatine Phosphokinase (Cpk) Content Is a Sensitive Incontrasting
confidence: 81%
“…The increased value of the microscopic group was significantly higher than that of the percutaneous transforaminal endoscopic group, and the difference was statistically significant, which was essentially consistent with the previous research results. In addition, some scholars have found that the postoperative serum CPK content of male patients is much higher than that of females due to their higher muscle tissue content [18] ; however, in this study, there was no significant difference between the serum CPK content of males and females, whether before or after surgery. For patients with high risk of lumbar spine surgery, some scholars suggest taking dynamic and systematic measurements of CPK contents and establishing a standard measurement interval to assess the degree of muscle injury more effectively [19] .…”
Section: Serum Creatine Phosphokinase (Cpk) Content Is a Sensitive Incontrasting
confidence: 81%
“…of Pat.MeanSDNr. of Pat.Zhang et al 2017 [14]7.9± 2.84810.1± 3.259Tschugg et al 2017 [16]13.7± 51919.1± 1248Kulkarni et al 2016 [17]4.11± 1.8365.84± 2.24925Hey et al 2015 [18]10.0257.725Terman et al 2014 [21]253321Wong et al 2014 [22]2.751444.4054Sulaiman et al 2014 [13]3.6± 1573.2± 0.211Singh et al 2014 [23]2.3± 1.2332.9± 1.133Gu et al 2014 [24]9.3± 3.74412.1± 3.638Brodano et al 2013 [25]4.1307.434Seng et al 2013 [26]3.6± 0.3405.9± 0.440Cheng et al 2013 [27]4.8± 1.8506.05± 1.825Lau et al 2013 [28]3.1± 1.7784.7± 2.149Parker et al 2013 [30]350450Adogwa et al 2012 [31]31447Pelton et al 2012 [33]2± 0.713333± 1.133…”
Section: Resultsmentioning
confidence: 99%
“…of Pat.Preoperative (mean ± SD)Last follow-up (mean ± SD)Nr. of Pat.Preoperative (mean ± SD)Last follow-up (mean ± SD)Yang et al 2017 [15]2143.5 ± 15.112.0 ± 6.42044.2 ± 14.313.5 ± 6.5Adogwa et al 2015 [19]4050.18 ± 16.7438.57 ± 25.5210849.15 ± 15.2134.27 ± 22.07Terman et al 2014 [21]5359 (−)44 (−)2158 (−)45 (−)Wong et al 2014 [22]14452.8 (−)18 (−)5451.2 (−)21 (−)Sulaiman et al 2014 [13]5753.7 (−)26.4 (−)1157.8 (−)46.1 (−)Gu et al 2014 [24]4443.7 ± 4.316.5 ± 2.03844.3 ± 5.215.9 ± 1.9Brodano et al 2013 [25]3042 ± 6.210 ± 6.63446 ± 7.112 ± 5.8Seng et al 2013 [26]4041.3 ± 20.113.6 ± 2.84042.1 ± 16.312.3 ± 1.9Rodriguez-Vela et al 2013 [29]2128.85 ± 5.5212.09 ± 7.592027.19 ± 8.1918.10 ± 12.45Parker et al 2013 [30]5032.3 ± 6.711.0 ± 9.45034.3 ± 7.915.6 ± 10.3Adogwa et al 2012 [31]1420.50 ± 7.76722.57 ± 9.3211.93 (−)Wang et al 2012 [32]4241.1 ± 10.318.2 ± 5.93940.217.4 ± 7.1Lee et al 2012 [6]7248.1 ± 18.821.4 ± 20.97244.4 ± 18.020.7 ± 16.5Parker et al 2012 [34]1536.9 ± 6.315.7 ± 8.91534.3 ± 11.517.1 ± 9.5…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ] All included studies were written in English or Chinese, and the full text was available. Ten studies were excluded because they included data from patients in previously published studies[ 37 38 39 40 41 42 43 44 45 46 ] and seven studies were removed because the included diseases did not fulfill the inclusion criteria. [ 47 48 49 50 51 52 53 ] One study had three subgroups, which were grouped by the number of surgery segments.…”
Section: R Esultsmentioning
confidence: 99%